The Impact of the Global Financial Crisis on the Banking System of Russia - Lyubov V. Borodacheva; Anatolii F. Goloborodov; Anna I. Guseva; Anna A. Drozdova; Maria P. Glyzina (International Journal of Economics and Financial Issues, 2016)
The problem of the functioning of the banking institutions in Russia and Central Eurasia in the context of their exposure to the global financial crisis. The crisis has become an integral part of the global economy. And the processes of globalization and integration have led to the fact that, originating in one state, in one economy, it is spreading to other countries and regions. Applying the methodology of historical and synchronous cross-country study suggests a mythological nature of the global financial collapse forecasts. But whenever any of the world's geo-economic zones, showed, unlike the others, who are in a state of crisis, high growth dynamics. There is therefore a need to study the impact of the crisis is in the regions, especially in terms of the functioning of banking institutions, as they are the backbone element of the economy. Bank Central Eurasia systems are in an unstable position, undergoing institutional transformation. It is therefore necessary to develop anti-crisis measures that will contribute to a smooth transition of regional economies from the crisis, to promote the sovereignty of the national currency, monetary integration, as well as the sustainability and stability of the functioning of the monetary and banking system.